PENGEMBANGAN PROGRAM PEMBELAJARAN INDIVIDUAL BAGI SISWA SLOW LEARNER DI SD LAB SCHOOL FIP UMJ - Haryati, Tuti; Winata, Widia; Suryadi, Ahmad (Universitas Muhammadiyah Jakarta, 2022)
ABSTRACTThe problem with implementing inclusive education at SD Lab School FIP UMJ is the school's lack of attention to teacher competence and administration prepared for slow learner students, and the absence of an Individual Learning Program. The purpose of this research is to see the development of academic ability (literacy) and independent behavior of slow learner students through the development of Individual Learning Programs. The benefit of the research is that the Individual Learning Program can help slow learner students in achieving long-term and short-term goals, and slow learner students are able to participate in learning activities based on their abilities and Basic Competencies (KD). The research was conducted in class 4.1 of SD Lab School FIP UMJ. The object of the research is slow learner students in grade 4.1 SD Lab School FIP UMJ. This research method uses mixed methods (R&D) research with the ADDIE instructional design model. Collecting data from observations, interviews and documentation. The results of research on the development of the Individual Learning Program in improving academic development (literacy) and independent behavior of slow learner students experience differences and changes between pre-development and post-development. The ability to read and write pre-development 32% while post-development 61%. Pre-development arithmetic ability is 40% while post-development is 74%. The ability to behave independently pre-development 38% while post-development 97%.ABSTRAKPermasalahan penyelenggaraan pendidikan inklusi di SD Lab School FIP UMJ adalah kurangnya perhatian sekolah terhadap kompetensi guru dan administrasi yang dipersiapkan kepada siswa slow learner, serta tidak adanya Program Pembelajaran Individual. Tujuan pelaksanaan penelitian ini untuk melihat perkembangan kemampuan akademik (literasi) dan prilaku mandiri siswa slow learner melalui pengembangan Program Pembelajaran Individual. Manfaat penelitiannya adalah dengan adanya Program Pembelajaran Individual dapat membantu siswa slow learner dalam menggapai tujuan jangka panjang dan jangka pendek, serta siswa slow learner mampu mengikuti kegiatan belajar berdasarkan kemampuan dan Kompetensi Dasar (KD) yang dimiliki. Penelitian dilaksanakan di kelas 4.1 SD Lab School FIP UMJ. Objek penelitiannya adalah siswa slow learner yang ada di kelas 4.1 SD Lab School FIP UMJ. Metode penelitian ini menggunakan penelitian mixed methods (R&D) dengan instructional design model ADDIE. Pengumpulan data dari hasil observasi, wawancara dan dokumentasi. Hasil penelitian pengembangan Program Pembelajaran Individual dalam meningkatkan perkembangan akademik (literasi) dan prilaku mandiri siswa slow learner mengalami perbedaan dan perubahan antara pra pengembangan dan pasca pengembangan. Kemampuan membaca dan menulis pra pengembangan 32% sedangkan pasca pengembangan 61%. Kemampuan berhitung pra pengembangan 40% sedangkan pasca pengembangan 74%. Kemampuan prilaku mandiri pra pengembangan 38% sedangkan pasca pengembangan 97%.